Предмет:
МатематикаАвтор:
аноним(3 *k + 4 * t)² – k² – 4 * k * t – 4 * t² = (3 *k+4 * t)² – (k² + 4 * k * t + 4 * t²) = (3 * k + 4 * t)² – (k + 2 * t)² = (3 *k + 4 * t + k + 2 * t) * (3 * k + 4 * t – k – 2 * t) = (4 * k + 6 * t) * (2 * k + 2 * t) = 2 * (2 * k + 3 * t) * 2 * (k + t) = 4 * (2 * k + 3 * t) * (k + t).
Ответ: (3 *k + 4 * t)² – k² – 4 * k * t – 4 * t² = 4 * (2 * k + 3 * t) * (k + t).
p² * (a – 2) – a² * (p – 2) = (p² *a – 2 * p²) – (a² *p + 2 * a²) = (p² *a – a² *p) – 2 * (p² + a²) = p * a * (p – a) – 2 * (p + a) * (p – a) = (p – a) * (p * a – 2 * (p + a)) = (p – a) * (p * a – 2 *p – 2 * a).
Ответ: p² * (a – 2) – a² * (p – 2) = (p – a) * (p * a – 2 *p – 2 * a).
Автор:
kristina99Добавить свой ответ
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть